Diabetes Results in Structural Alteration of Chondroitin Sulfate in the Urine - Tingting Zhao; Xiaoguang Lu; Neal M Davies; Yuewen Gong; Jingzhen Guo; Haojun Zhang; Zhiguo Li; Jing Hong; Guixiang Fu; Ping Li (Frontiers Media S.A., 2013)
Purpose. The assessment of the clinical significance of chondroitin sulfate in patients with type 2 diabetes mellitus (T2DM) and diabetic nephropathy (DN) for the detection of the relationship between chondroitin sulfate (CS) structure and disease. Methods. Healthy control (n=15), type 2 diabetic patients with normalbuminuria (n=12), and patients with microalbuminuria (n=13) were enrolled in the study. Total sulfated glycosaminoglycans (GAGs) concentration in the first morning urine was evaluated by 1,9-dimethylmethylene blue method and the composition was determined by agarose gel electrophoresis. Urinary chondroitin sulfate was quantified by a combination of treatment with specific lyase digestions and separation of products by SAX-HPLC. Results: GAGs concentration significantly increased in diabetic patients with microalbuminuria compared to diabetic patients with normalbuminuria. Qualitative analysis of urinary GAGs revealed the presence of chondroitin sulfate, heparan sulfate, and low-sulphated chondroitin sulphate-protein complex (LSC-PG). There was a decrease in CS and an increase in LSC-PG in the urine of patients with diabetes compared to healthy controls. Moreover, in diabetic patients, chondroitin sulfate contains more 6-sulfated disaccharide and less 4-sulfated disaccharide. There was a statistically significant difference in ratio of 6-sulfated disaccharide to 4-sulfated disaccharide among the three groups. Conclusions: GAGs were significantly increased in diabetic patients with microalbuminuria. The levels of urinary GAGs, ratio of LSC-PG/CS, as well as ratio of 6-sulfated to 4-sulfated disaccharides could be useful markers for diagnosis of patients with diabetic nephropathy.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.